Tyrosine Kinase Inhibitor Sunitinib Delays Platelet-Induced Coagulation: Additive Effects of Aspirin - Tullemans, Bibian M. E.; Fernández, Delia I.; Veninga, Alicia; Baaten, Constance C. F. M. J.; Peters, Linsey J. F.; Aarts, Maureen J. B.; Eble, Johannes A.; Campello, Elena; Spiezia, Luca; Simioni, Paolo; van der Vorst, Emiel P. C.; van der Meijden, Paola E. J.; Heemskerk, Johan W. M.; Kuijpers, Marijke J. E. (Thrombosis and Haemostasis, 2021)
Background Sunitinib is a multitarget tyrosine kinase inhibitor (TKI) used for cancer treatment. In platelets, sunitinib affects collagen-induced activation under noncoagulating conditions. We investigated (1) the effects of sunitinib on thrombus formation induced by other TK-dependent receptors, and (2) the effects under coagulating conditions. Cardiovascular disease is a comorbidity in cancer patients, resulting in possible aspirin treatment. Sunitinib and aspirin are associated with increased bleeding risk, and therefore we also investigated (3) the synergistic effects of these compounds on thrombus and fibrin formation.Methods Blood or isolated platelets from healthy volunteers or cancer patients were incubated with sunitinib and/or aspirin or vehicle. Platelet activation was determined by TK phosphorylation, flow cytometry, changes in [Ca2+]i, aggregometry, and whole blood perfusion over multiple surfaces, including collagen with(out) tissue factor (TF) was performed.Results Sunitinib reduced thrombus formation and phosphatidylserine (PS) exposure under flow on collagen type I and III. Also, sunitinib inhibited glycoprotein VI-induced TK phosphorylation and Ca2+ elevation. Upon TF-triggered coagulation, sunitinib decreased PS exposure and fibrin formation. In blood from cancer patients more pronounced effects of sunitinib were observed in lung and pancreatic as compared to neuroglioblastoma and other cancer types. Compared to sunitinib alone, sunitinib plus aspirin further reduced platelet aggregation, thrombus formation, and PS exposure on collagen under flow with(out) coagulation.Conclusion Sunitinib suppresses collagen-induced procoagulant activity and delays fibrin formation, which was aggravated by aspirin. Therefore, we urge for awareness of the combined antiplatelet effects of TKIs with aspirin, as this may result in increased risk of bleeding.
Keywords: platelets; thrombus; tyrosine kinase inhibitor; sunitinib; procoagulant activity; aspirin